Improved protease digestion conditions for membrane protein detection. Issue 15 (10th June 2015) - Min, Lie; Choe, Leila H.; Lee, Kelvin H.; Lapizco‐Encinas, B. H.; Hayes, M. A.
<x xml:space="preserve">Abstract</x> This work presents improved protease digestion conditions for membrane protein detection. The enzymatic digest of bacteriorhodopsin (BR), a model membrane protein with seven transmembrane domains (TMDs) was investigated. An initial in‐gel digestion identified 17% BR sequence coverage, including part of the seventh TMD. To improve sequence coverage, BR digest was tested with different concentrations of RapiGest, methanol (MeOH) and SDS using either trypsin or chymotrypsin. Two improved conditions, 0.01% SDS or the combination of 10% MeOH and 0.01% RapiGest, were chosen. Trypsin digestions in both conditions achieved more than 40% BR sequence coverage compared to 0% using standard digestion conditions. Peptides detected from trypsin and chymotrypsin digestions in the same condition were combined to maximize sequence coverage. The same conditions were applied to a different membrane protein with one TMD, Selenoprotein S, and proteins from Escherichia coli. For Selenoprotein S, a higher sequence coverage, including a peptide from the TMD, was detected from the improved condition compared to the typical condition. The application of both improved conditions to a membrane protein fraction of Escherichia coli resulted in the identification of 309 (SDS) and 329 (MeOH/RapiGest) unique proteins of which 140/309 and 148/329 were membrane proteins.